Effect of Cow’s-milk-free Diet on Pediatric Chronic Constipation (Journal of Armed Forces Medical College, Bangladesh, 2026)
Background: Chronic constipation in children can severely impact the quality of life. Emerging evidence suggests a potential link between dietary factors, such as cow's milk and constipation. Some studies suggest that cow's-milk-free diets (CMFD) may alleviate symptoms in pediatric patients.Objective: This study aimed to investigate the effect of cow’s milk-free diet on pediatric chronic constipation.Methods: This randomized control trial was conducted at the Department of Pediatrics, Combined Military Hospital, Dhaka, Bangladesh from June 2024 to December 2024. The study involved the enrollment of 60 children aged between 4 to 14 years, all of whom had been managed by using laxatives for a minimum of 3-months tenure without any improvement and met the Rome IV criteria for chronic constipation. The participants were assigned (Randomly) into two groups. The case group (30 participants) received (Taken) a cow's milk-free diet (CMFD) and calcium supplements for 4 weeks, while the participants (n=30) of another group (Control) had no restrictions on cow's milk or dairy products. The data were analyzed by using SPSS v26.0 software.Results: In this study, comparing the Rome criteria of the control group before and after the 4-week trial, no significant difference was found, except for the parameter "The presence of a large fecal mass in the rectum" (p=0.032). Conversely, comparing the Rome criteria (RC) of the case group before and after the 4-week trial, significant differences were found in the scores for all parameters, with p-values less than 0.001.Conclusion: Children having chronic constipation (CC) that does not cure or respond to laxative treatment may get benefit from a CMFD (Cow's milk-free diet) and dairy-free diet. Some children can experience notable improvements in bowel function and overall health by removing CMFD and dairy products from their diet.JAFMC Bangladesh, Vol 21, No 2 (December) 2025:22-25